Field Case: Application of Polyamine Based Mud System to Drill Kintom Formation in Sulawesi and Comparison to Conventional KCl-Polymer Mud System - Dominico Alphan Setyanto; Rachmat Sudibjo; Abdul Hamid (Penerbitan Universitas Trisakti, 2018)
Drilling mud has a vital role in onshore or offshore oil and gas drilling operations with its primary function as the hydrostatic pressure to balance the formation pressure. There are some formations in Indonesia where the drilling hazards are extensive, but the problem that most likely to overcome is the shale/clay swelling. Today there is a water based mud called Polyamine Mud, a Polyamine mud has the advantages over conventional water base mud and also in some functions are as good as the Oil Base Mud. Some companies are still trying to adopt this technology into their drilling projects with various aspects to be considered and are wondering whether it will help them to drill a formation with shale/clay problem characteristics. A field location on the island of Sulawesi has drilled some wells on the Kintom formation using the Polyamine mud for a total depth of about 7,000 ft – 9,000 ft. The drill hole problem was not only the shale/clay swelling, but was also followed by some problems such as differential sticking and partial to total mud losses. The wells have now been drilled successfully and the gas production was above expectation. This paper will discuss a comparison of the Polyamine mud with the conventional mud system such as KCL-Polymer mud by doing some unconventional tests in the laboratory, including inhibition test, dispersion test, accression test, and bulk hardness test. After being tested in the laboratory, the Polyamine 3% mud system has drilled succesfully in some wells.